Envelhecimento e proteção cognitiva: influências da escolaridade e da aptidão física - TORRES, Natáli Valim Oliver Bento (Universidade Federal do Pará, 2017)
Clinical and hematological evaluations were used to study the influence of age, formal education and physical fitness on cognitive performances of two aged groups. For this purpose, three independent experiments were designed. In the first we investigated the influences of age and low education on cognitive performance of healthy elderly. In the second we investigated possible associations between cognitive age-associated cognitive decline, level of physical activity and platelet volume, an indirect peripheral marker of inflammation. In the third we compared age matched healthy elderly with Alzheimer's disease patients, where it is promptly recognized the contribution of inflammation to accelarate disease progression. To measure the influence of education, we used selected tests of the Cambridge Automated Neuropsychological Battery (CANTAB), minimizing the influence of socio-cultural and educational variables, usually present in classical (paper and pencil) psychometric procedures. Thus, sustained visual attention, reaction time, spatial working memory and episodic learning and memory were measured in 182 elderlies. Based on medical history, visual acuity examination and mini-mental state examination (MMSE) we established inclusion criteria as follow: visual acuity 20/30 or higher, no previous or current history of head trauma, stroke, chronic alcoholism, neurological diseases, subjective complains of memory and absence of psychiatric illness, including major depression. Also excluded the volunteers with clinical and / or hematological signs of active infection. Subjects were grouped according to the education level (1 to 7 and ≥ 8 years of schooling) and age (60-69 and ≥ 70 years of age). Two-way analysis of variance indicated that, on average, education influenced performances on visual attention, learning and memory, reaction time and spatial working memory and age influenced the latency on reaction time test. The results suggest that improvement of education should be one of the targets of preventative actions to minimize age-related cognitive decline and that CANTAB might be used to detect subtle cognitive decline in healthy aging. In the study that measured potential associations between platelet morphological changes, physical activity and age-related cognitive decline, we adopted the same exclusion criteria used in the first assay and evaluated 152 healthy elderlies. International Physical Activity Questionnaire (IPAQ - long form) and physical fitness was adopted as indicators of physical activity levels. Physical fitness was assessed by measurements of agility, muscle strength of lower limbs and aerobic capacity. The inclusion criteria based on physical activity self-report only included volunteers performing supervised physical activities at least three times a week, while the inclusion of sedentary elderly demanded that such activities have been not conducted for six consecutive months preceding assessment. All volunteers who participated in the study showed normal test scores of MMSE. Compared to the sedentary group, active elderly showed significant higher performance in all physical tests, sustained visual attention and reaction time, and these results were associated with lower platelet volumes. Significant correlations were found between platelet volumes and performances on learning and memory, rapid visual processing and sustained attention. In the study comparing the platelet morphology of patients with Alzheimer's disease with healthy elderly individuals we found that AD volunteers showed significantly higher platelet volumes associated with poor performance in MMSE. Taken together the results show that physical fitness and physical activity are associated with lower platelet volume and less cognitive decline during aging. The major and minor mean platelet volumes found respectively in patients with Alzheimer's disease and elderly who exercise regularly, suggests that this parameter, usually ignored in haematological routine analysis, appears to have potential value to encourage preventative actions.